THE RELATIONSHIP OF CREDIT CHARACTERITICS AND COAL PRICE WITH REPAYMENT CAPACITY: CASE STUDY OF A HEAVY EQUIPMENT LEASING COMPANY - Subekti, Hanifa Endru; Faturohman, Taufik (Journal of Business and Management, 2017)
Abstract. Deputy of OJK also said that in 2015, heavy equipment leasing company has the highest level of non-performing financing (NPF) compared to other leasing with 4.34%. This research has an aim to find the determinants of NPF in a heavy-equipment leasing company. The method used is multi-linear regression and logistic regression. This research used two methods because the dependent variable could be interpreted using two ways, continuous variables and binary. The independent variables used are amount of financing, amount of security deposit, effective rate, tenor, percentage of financing, age of contract and coal price. For the dependent variable used is the NPF status itself drawn from the lesseeâ€™s maximum overdue days. The result for multi-linear regression shows amount of financing, tenor, percentage of financing and coal price have positive relationship with NPF. Also, age of contract has negative relationship with NPF. Logistic regression result shows that percentage of financing and tenor have positive relationship with NPF and age of contract has negative relationship with NPF. The result of this research aim to help the company in risk-profiling their lessee, also help the future research to broaden the research subject for this type of research.Â Keywords: determinants, heavy-equipment, leasing, NPF, repayment capacity